Lehmann Isaac Kohen, Grandson of Behrend Lehmann and Student of Albrecht Haller: The (Rightful) First Jewish Medical Graduate of the University of Göttingen, 1739 - Reichman, Edward (2025)
From the time of the establishment of universities in Europe, Jews were barred from university medical training by papal decree. By the fifteenth century, the University of Padua in Italy opened its doors to Jews, followed by Dutch universities in the mid seventeenth century. While Tuviya HaRofeh and Gabriel Felix briefly attended the University of Frankfurt in 1678, it wasn't until the early to mid-eighteenth century that German universities followed suit. Here we identify the first Jewish medical graduate of one of Germany's premier medical schools, the University of Göttingen. While Benjamin Wolff Gintzburger is thought by many to have been the university's first Jewish graduate, we clarify here that it was in fact Lehmann Isaac Kohen, grandson of the Court Jew Behrend Lehmann. The expansive archival record of Kohen's medical training is unique among Jewish medical students of the Early Modern Period. Kohen was a student of the renowned Albrecht von Haller, and it was in an addendum to Kohen's dissertation that Haller made an extraordinary statement, ignored in the historical literature, advocating religious tolerance in medical education.
Keywords: Jews; Juden; Lehmann Isaac Kohen; University of Göttingen; Universität Göttingen